Análisis financiero de la Empresa Credigas Koko's E.I.R.L. comercializadora de gas para uso doméstico y su incidencia en la reducción de riesgos y mejora de la situación económica y financiera, año 2016 - Cabanillas Vásquez, Miguel Angel (2017)
The present research work has for purpose to apply the financial analysis to the Annual Accounts of the years 2014 and 2015 of the company CREDIGAS KOKO'S E.I.R.L, and determining his incidence in risk reduction and improvement of the economic situation and finance company, year 2016. The material of study fixes it the sample represented by the company CREDIGAS KOKO'S E.I.R.L, in the present research work the descriptive method was used. In the application of the financial analysis the method of vertical analysis, the method of horizontal analysis and the use of financial ratios were used. Also the techniques of the interview and the bibliographic investigation were used, in like manner the techniques of treatment and analysis of information were used, in kind the techniques of data processing were used. It is concluded that the application of the financial analysis affects favorably because it allows the Manageress (legal representative) establishing the economic situation and real company finance company, likewise it allows determining the presence of financial risks that the company in the development of her commercial transactions faces. It is recommended to the Manageress (legal representative) apply the company financial analysis periodically, to evaluate the financial diagnoses (reports) and to take the opportune decisions that are enabled developing an efficient financial planning with the main objective to strengthen the entrepreneurial policies and to face the presence of the financial risks in the company adequately.